Proximate Composition in Some Species of Fish and Seafood Available on the Costa Rican Pacific Ocean - Fonseca-Rodríguez, Cristian (2017)
Fish and shellfish are the most complete foods due to their quality and quantity of nutrients. However, little is known about the chemical composition of the fishery resources of the Costa Rican Pacific Ocean. Therefore, this study aims to determine the nutritional potential of the (fresh) edible parts of six seafood species for consumption and with commercial importance in the Pacific area of Costa Rica. The proximate composition analysis—moisture, ash, ether extract and protein—were determined by AOAC methodology. The results indicated that the moisture content ranged from 77.13% for barracuda (Sphyraena ensis) and 83.12% for squid (Lolliguncula panamensis); ash was between 0.84% for squid and 1.65% for freshwater mussel (Anodonta luteola); the ether extract, from 1.16% for squid and 2.24% for freshwater clam. The freshwater clam had the lowest percentage of protein (10.73%); while the sole (Cyclopsetla querna) showed the highest percentage (19.86%). The studied species are a good alternative for human consumption due to their low fat and protein intake.